THE EFFECT OF LEADERSHIP STYLE AND COMPENSATION ON ORGANIZATIONAL COMMITMENT OF BABINSA IN JAKARTA - Syahchari, Dicky Hida; Kurnia, Lifany Husnul (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2018)
This study investigates the conceptualization of the leadership style and compensation within organizational commitment of Babinsa in Jakarta asÂ wellÂ as examiningÂ theÂ Â leadership style and compensation Â on Â organizational commitment byÂ previousÂ researchers. This study use qualitative method byÂ reviewingÂ andÂ integratesÂ previousÂ studiesÂ toÂ pointÂ toÂ theÂ significanceÂ ofÂ theÂ Â leadership style and compensation towards organizational commitment of Babinsa specifically in Â Jakarta. ThisÂ study proposesÂ aÂ researchÂ frameworkÂ toÂ investigateÂ theÂ relationshipÂ of Â leadership style and compensationÂ on organizational commitment of Babinsa in Jakarta. The study isÂ particularlyÂ useful forÂ practitionersÂ byÂ identifyingÂ advantagesÂ ofÂ suitableÂ organizational commitment of Babinsa in Jakarta.Â Â